Ikkīsavīṃ sadī kā navya vimarśa - Dube, Rekhā (Paṅkaja Buksa, 2021)
Contributed articles on the depiction of transgender and intersex people in 21st century Hindi fiction and their social conditions.
Includes bibliographical references
Keywords: Aufsatzsammlung; Hindi fiction; 21st century; History and criticism.; Transgender people in literature.; Intersex people in literature.; Transgender people; India; Social conditions.; Intersex people; India; Social conditions.